Basics of Ankle Arthroscopy Part 6: Peroneal Tendoscopy: Surface Anatomy, Portal Placement, and Diagnostic Evaluation - James J. Butler, M.B., B.Ch.; Steven Magister, M.D.; Taylor Wingo, M.D.; Brittany DeClouette, M.D.; Sebastian Krebsbach, B.S.; John G. Kennedy, M.D., M.Ch., M.M.Sc., F.F.S.E.M., F.R.C.S. (Orth) (Arthroscopy Techniques)
Peroneal tendoscopy is an important diagnostic and therapeutic tool in the treatment of pathologies of the peroneal tendon. In this article, the basics of peroneal tendoscopy are reviewed, including the relevant surface anatomy, portal placement, and diagnostic tendoscopic techniques. We also compare the benefits and limitations associated with performing this peroneal tendoscopy with a 1.9-mm 0° needle endoscope compared to using a 2.7-mm or 4.0-mm 30° endoscope.